Narrowing Racial Differences in Trust: How Discrimination Shapes Trust in a Racialized Society. (17th July 2021) - Evangelist, Michael
Abstract: In the United States, survey research and qualitative studies consistently find that people of color—and Blacks in particular—report substantially lower levels of trust than do whites. These racial differences in trust pervade a range of social contexts, from interpersonal relationships with friends, family, and neighbors to interactions with the health care and criminal justice systems. Scholars often attribute racial differences in trust to historical and contemporary forms of discrimination, yet few studies have assessed the relationship among race, discrimination, and trust in the context of the United States. Using the Chicago Community Adult Health Study, I examine how the experience of discrimination relates to generalized trust, trust in neighbors, and trust in community police. Findings reveal that personal experience with discrimination contributes modestly to racial differences in trust. In fact, the negative association between discrimination and generalized trust appears strongest for whites. These findings suggest that understanding distrust requires a richer conceptual framework that moves beyond personal experience with discrimination. I argue that the theory of systemic racism provides a framework for understanding distrust as a consequence of countervailing efforts to uphold and contest the racial hierarchy.